1991
DOI: 10.1111/j.1600-0560.1991.tb01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Medusa head‐like granules in squamous cell carcinoma with differentiation toward a hair follicle structure

Abstract: A case of squamous cell carcinoma (SCC) with regional lymph node metastasis in a 69-year-old Japanese man is reported. The tumor was characterized by the proliferation of peripheral basaloid, inner squamoid, and glycogen-rich cells, the presence of trichilemmal keratinization, and the presence of ladder-like, membrane-coating granules. These findings suggested that this tumor differentiates toward a hair-follicle structure. The most interesting feature of this tumor was the presence of medusa head-like granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…[182][183][184] Follicular squamous cell carcinoma Although most SCCs arise in the epidermis, occasional cases of SCC arising in hair follicles have been reported. [186][187][188] It has long been known that SCC can arise from follicular epithelium, and the cases have shown both squamous as well as follicular and sebaceous differentiation. 7,186 Diaz-Cascajo et al 187 recently reported 16 cases of SCC developing in hair follicles, most arising in sun-damaged skin, typically on the face of elderly persons.…”
Section: Pigmented Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…[182][183][184] Follicular squamous cell carcinoma Although most SCCs arise in the epidermis, occasional cases of SCC arising in hair follicles have been reported. [186][187][188] It has long been known that SCC can arise from follicular epithelium, and the cases have shown both squamous as well as follicular and sebaceous differentiation. 7,186 Diaz-Cascajo et al 187 recently reported 16 cases of SCC developing in hair follicles, most arising in sun-damaged skin, typically on the face of elderly persons.…”
Section: Pigmented Squamous Cell Carcinomamentioning
confidence: 99%
“…A broadspectrum anti-HPV antibody was also negative in all cases. 187 Yamamoto et al 188 reported a case of SCC with differentiation toward follicular epithelium, demonstrating both squamoid and glycogen-rich cells, with tricholemmal keratinization and so-called 'medusa head' granules. The later was a unique finding, suggesting differentiation toward the innermost cells of the outer root sheath.…”
Section: Pigmented Squamous Cell Carcinomamentioning
confidence: 99%
“…This has prompted some dermatopathologists to advance the opinion that PTT is a low‐grade adnexal carcinoma 6 or merely a variant of squamous cell carcinoma 7 . Indeed, squamous cell carcinoma has been always considered to be the main differential diagnosis of PTT, 4 and in small samples the distinction can be almost impossible, moreover taking into account that some squamous cell carcinomas can display features of hair follicle differentiation 8 …”
Section: Introductionmentioning
confidence: 99%
“…Microcystic adnexal carcinoma has characteristic histological appearances including both pilar and eccrine differentiation (8,9). Squamous cell carcinoma can contain specific structures suggesting pilosebaceous or glandular differentiation (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%